If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + 1 = 6(x + 4) Reorder the terms: 1 + Y = 6(x + 4) Reorder the terms: 1 + Y = 6(4 + x) 1 + Y = (4 * 6 + x * 6) 1 + Y = (24 + 6x) Solving 1 + Y = 24 + 6x Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + Y = 24 + -1 + 6x Combine like terms: 1 + -1 = 0 0 + Y = 24 + -1 + 6x Y = 24 + -1 + 6x Combine like terms: 24 + -1 = 23 Y = 23 + 6x Simplifying Y = 23 + 6x
| -7x-12=x | | -5(-5m+7)-8m=-171 | | 7(7n+6)=91 | | 2x^2+5x=5+3x-2x^2 | | N+.11=2n | | 2x+8i=6-(2y)I | | 5x-4=-2+(2x+1) | | -8(x+6)=-112 | | 2(-6n+1)=-94 | | -16=4(a-3) | | 3/8-1/6= | | 6a+4-9a=10-a | | 6x-3y=-72 | | -8(3-8k)=104 | | -2x+7x+30=15 | | 5x-31=4x-10 | | 5x-3q=4x-10 | | 6h+5=-30-h | | 8x^6+5x^3+1=0 | | 1/8x-y=7 | | (3a^2+5a-4)-(3a^2-4a+1)=4a+15 | | 5(3-2n)=85 | | 9-2x-9-16x=14x-7-4x-11 | | 19x+-9x+-11=19 | | 3g+26=g+10 | | 4(4x-3)=100 | | -9(y+1)=3(y-3)-36 | | pr+qs=4 | | 0.1888888888888888888888888888888888= | | 37.68=(2)(3.14)(x+1) | | -5(2x-3)-5x=120 | | 8-3(x+4)=2x+1 |